Comparative Politics of Southeast Asia An Introduction to Governments and Political Regimes - Croissant, Aurel; Lorenz, Philip; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This textbook provides a comprehensive introduction to the political systems of all ASEAN countries and Timor-Leste from a comparative perspective. It investigates the political institutions, actors and processes in eleven states, covering democracies as well as autocratic regimes. Each country study includes an analysis of the current system of governance, the party and electoral system, and an assessment of the state, its legal system and administrative bodies. Students of political science and regional studies will also learn about processes of democratic transition and autocratic persistence, as well as how civil society and the media influence the political culture in each country. .
Government and Political Regimes in Southeast Asia: An Introduction -- Brunei Darussalam: Malay Islamic Monarchy and Rentier State -- Cambodia: From UN-Led Peace-Building to Post-genocidal Authoritarianism -- Indonesia: Challenges of Conflict and Consensus in the Era of Reformasi -- Laos: The Transformation of Periphery Socialism -- Malaysia: Competitive Authoritarianism in a Plural Society -- Myanmar: The Challenging Transition from Military to Democratic Government -- Philippines: People's Power and Defective Elite Democracy -- Singapore: Contradicting Conventional Wisdom About Authoritarianism, State and Development -- Timor-Leste: Challenges of Creating a Democratic and Effective State -- Vietnam: The Socialist Party State -- Conclusions: Comparing Governments and Political Institutions in Southeast Asia. .
Keywords: Comparative government; Asia Politics and government; Political science; Elections; Ethnology Asia; Culture; Southeast Asia History; Comparative Politics; Asian Politics; Political Science; Electoral Politics; Asian Culture; History of Southeast Asia